A Critical Overview on Organizational Entrepreneurship with Focus on Identifying Components and Obstacles - Farzad Ziviar; Abolfazli Farahani; Loghman Keshavarz (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
It is documented that environmental subjects of organizations need innovational solutions to solve their problems. Undoubtedly, creativity and innovations which means organizational entrepreneurship are most important keys in this way.Organizational entrepreneurship means developing capabilities and opportunities inside an organization through combining new resources. So, new organizations consider organizational entrepreneurship as a key element which boosts competitive advantages in organization. This paper aims to criticize and identify the organizational entrepreneurship’s barriers in Ministry of Sport & Youth. To this end, this paper considers a comprehensive review literature with a focus on Schupeter, Frai, Vesper et al.’s point of views. Thirty components in 3 dimensions of structural, behavioral, and contextual were considered in this paper, including 66 obstacles in order to criticize in Ministry of Sport and Youth.It is suggested that managers and researchers in Ministry of Sport andYouth evaluate and implement the aforementioned  components and obstacles.